2009
DOI: 10.1007/s00039-009-0713-z
|View full text |Cite
|
Sign up to set email alerts
|

Minors in Expanding Graphs

Abstract: 1 corresponding vertices u i , u j of Γ are connected by an edge. A graph G = (V, E) is (t, α)-expanding if every subset X ⊂ V of size |X| ≤ α|V |/t has at least t|X| external neighbors in G. A graphfor every subset X ⊆ V , where e(X) stands for the number of edges spanned by X in G. Informally, this definition indicates that the edge distribution of G is similar to that of the random graph G |V |,p , where the degree of similarity is controlled by parameter β.Here are the main results of this paper.Theorem 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 36 publications
3
45
0
Order By: Relevance
“…An answer to the problem would indicate whether expansion alone is sufficient when trying to force a complete minor of the largest possible order in a sparse graph, or whether other parameters are also relevant. Krivelevich and Sudakov [13] showed that we do have ccl(G) ≥ c n/ log n. (They also considered the case when t is not bounded but grows with n.) As observed in [13], this bound can also be deduced from a result of Plotkin, Rao, and Smith [19] on separators in graphs without a large complete minor. Kleinberg and Rubinfeld [12] also considered the same problem but with a weaker definition of expansion.…”
Section: Open Questionsmentioning
confidence: 68%
See 2 more Smart Citations
“…An answer to the problem would indicate whether expansion alone is sufficient when trying to force a complete minor of the largest possible order in a sparse graph, or whether other parameters are also relevant. Krivelevich and Sudakov [13] showed that we do have ccl(G) ≥ c n/ log n. (They also considered the case when t is not bounded but grows with n.) As observed in [13], this bound can also be deduced from a result of Plotkin, Rao, and Smith [19] on separators in graphs without a large complete minor. Kleinberg and Rubinfeld [12] also considered the same problem but with a weaker definition of expansion.…”
Section: Open Questionsmentioning
confidence: 68%
“…For this, they determined the likely value of ccl(G n,p ) for the random graph G n,p with constant edge probability p and compared this with known results on χ(G n,p ). Krivelevich and Sudakov [13] investigated ccl(G) for expanding graphs G and derived the order of magnitude of ccl(G n,p ) from their results when p = n −c , with c < 1. In [9], we extended these results to any p with pn ≥ c for some constant c > 1, which answered a question from [13].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Otherwise we would get a 4-cycle by counting the number of edges between S and its boundary N (S)\S. This simple observation appears to be a powerful tool in attacking various extremal problems and was used in [26] and [21] to resolve several conjectures about cycle lengths and clique-minors in H-free graphs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is not hard to show (see, e.g., [21]) that if G is a K s,t -free graph (s ≥ t) with minimum degree d, then all subsets of G of size at most d 1/(t−1) expand by a factor of Θ(d/s). Therefore, K s,t -free graphs with minimum degree d contain all trees of order Ω d 1+1/(t−1) and maximum degree O(d/s).…”
Section: Discussionmentioning
confidence: 99%